Multi-centered Comparison of Patient Reported Outcomes After Hip Arthroscopy versus Combined Hip Arthroscopy Alone and Peri-acetabular Osteotomy in Patients with Acetabular Dysplasia. Issue 7 (21st July 2017) - Domb, Benjamin G.; Kenney, Raymond James; Cook, Christopher; LaReau, Justin M.; Childs, Sean; Chaharbakhshi, Edwin; Giordano, Brian D.
Objectives: The purpose of this study was to compare prospectively collected patient reported outcomes (PRO) data in patients undergoing Hip Arthroscopy alone versus combined Hip Arthroscopy and Peri-acetubular Osteotomy (HA/PAO). Methods: Prospectively collected PRO data was reviewed in patients enrolled in IRB approved studies at two high volume hip preservation centers who underwent either Hip Arthroscopy alone or combined HA/PAO. Patients were included who had a lateral center edge angle <25 degrees, completed pre-operative and a minimum of 1 year post-operative PRO data. Questionnaires were administered to patients at intervals including pre-operative, 3 months, 1 year and 2 years post-operative. Questionnaires were composed of validated PRO scores: modified Harris Hip Score (mHHS), Hip Outcome Score (HOS) Activities of Daily Living (ADL) and Sports subscales, Non-arthritic Hip Score (NAHS) and Pain Visual Analog Scale (VAS). Results: Prospectively collected data was reviewed for 91 patients who underwent Hip Arthroscopy and 34 patients who underwent HA/PAO. Average age at the time of surgery was 32 years old (range 14-62) for arthroscopy and 31 years old (range 15-51) for combined surgery. Hip Arthroscopy patients were 35% male and 65% female. HA/PAO patients were 15% male and 85% female. PRO data for Hip Arthroscopy, reported as averages with 95% confidence intervals in parentheses at pre-operative, 3 months, 1 year and 2 years post-operatively. mHHS: 66.3 (3.1), 83.8 (3.5), 84.3 (4.1), 84.4 (3.4). HOS ADL: 70.1 (4.0), 85.3 (3.2), 87.1 (4.2), 87.4 (4.0). HOS Sports: 47.3 (4.6), 64.7 (6.6), 73.7 (8.1), 75.2 (5.9). NAHS: 65.5 (3.7), 80.1 (3.3), 83.8 (4.5), 83.8 (3.9). Pain VAS: 5.4 (0.5), 2.6 (0.5), 2.5 (0.6), 2.6 (0.6). PRO data for HA/PAO, reported as averages with 95% confidence intervals in parentheses at pre-operative, 3 months, 1 year and 2 years post-operatively. mHHS: 51.1 (4.6), 58.7 (7.9), 71.7 (7.3), 74.7 (13.1). HOS ADL: 58.3 (6.5), 65.7 (9.0), 83.6 (9.8), 85.1 (18.7). HOS Sports: 41.7 (7.2), 38.0 (11.7), 72.5 (11.5), 79.3 (11.9). NAHS: 56.7 (5.2), 71.6 (5.3), 80.2 (7.7), 83.4 (11.8). Pain VAS: 5.3 (0.9), 1.9 (0.8), 2.2 (1.0), 1.0 (0.9). Conclusion: Both cohorts had significant improvement in all PRO measures at 1 and 2 years when compared to pre-operative PRO measures. HA/PAO patients had significantly lower mHHS and HOS ADL pre-operatively; NAHS approached significance. HOS Sports and Pain VAS had no significant pre-operative differences between groups. At 3 months, the HA/PAO patients had significantly lower mHHS, HOS ADL and HOS Sports, while again NAHS approached significance. There was no significant difference in Pain VAS at 3 months. Only the mHHS remained significantly lower for the HA/PAO patients at 1 year. At 2 years, only Pain VAS showed significantly better pain scores for HA/PAO patients, although lacking clinical significance. All other PRO measures showed no significant difference at 2 years. Patients who underwent HA/PAO had significantly lower pre-operative and early post-operative PRO measures. HA/PAO patients, however, reached similar values for PRO measures by 1 year; only the mHHS remained lower. At 2 years, neither group showed statistical or clinical difference in PRO measures.